Effect of moisture on static and fatigue strength of rubberwood/ recycled polypropylene composites - Mustafa, Zaleha; Tuan Nawi, Tuan Idzuddin; Sheikh Md Fadzullah, Siti Hajar; Nordin, Mohd Nur Azmi; Ratanawilai, Thanate (Semarak Ilmu Publishing, 2024)
While the field of plant fibre composites is experiencing rapid growth in research and development, there are still essential considerations that must be addressed before these materials can be adopted by industries for structural applications. One of the primary concerns revolves around their durability. This study aims to assess how moisture affects the static and fatigue behaviour of a rubberwood/recycled polypropylene composite. The specimens were exposed to a humid environment at 23 °C in water immersion for 30 days. Quasi-static and tension-tension fatigue tests were carried out. Results show that exposure to moisture has caused a significant decrease in their initial quasi-static strength and stiffness. The fatigue strength, on the other hand, has been enhanced. The fatigue strength coefficient decreases by more than half after ageing, suggesting a less pronounced decrease in maximum stress as the number of cycles increases. The fatigue hysteresis loop and evolution of the secant modulus of non-aged composite show more pronounced fatigue damage when compared to the aged composite.